Detection of antibiotic resistant Enterobacterales in commercial raw pet food: a preliminary study - Fisher, Carolyn D.; Call, Douglas R.; Omulo, Sylvia (Frontiers in Veterinary Science, 2024)
Raw diets have become popular in companion animal nutrition, but these diets may be contaminated with harmful bacteria because heat processing is not utilized to mitigate pathogens during the production process. We analyzed 24 commercially available frozen raw canine and feline diets for extended-spectrum beta-lactamase-producing Enterobacterales (ESBL-E). Samples were incubated in tryptic soy broth augmented with 50 μg/mL ampicillin to enrich for ESBL-E. ESBL-E were isolated using CHROMagar ESBL plates and isolate identification and antibiotic susceptibility testing were confirmed using the VITEK®2 instrument. ESBL-E were isolated from 42% (10/24) of raw diets, with E. coli, Enterobacter cloacae complex and Klebsiella pneumoniae predominating. Most ESBL-E isolates (71%, 32/45) were multidrug-resistant. Direct plating of samples onto tryptic soy agar yielded bacterial counts >6 log10 for 2 samples from two different manufacturers. This preliminary study justifies further investigation into the potential contribution of raw diets to the dissemination of antibiotic resistant bacteria in companion animals and domestic living spaces.